2019
DOI: 10.3390/ma12182874
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light-Burnt Dolomite Incorporation on the Setting, Strength, and Drying Shrinkage of One-Part Alkali-Activated Slag Cement

Abstract: This study investigates the potential of light-burnt dolomite (LBD) as a supplementary cementitious material with ground granulated blast furnace slag (GGBFS) and Ordinary Portland cement (OPC). In this work, LBD was substituted for up to 20% of GGBFS in sodium sulfate-activated slag systems. The effects of LBD incorporation on the flow, setting time, compressive and flexural strength development, and drying shrinkage were explored with, X-ray diffraction and thermogravimetric analyses. LBD incorporation resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The alkali cations present in the binding gels (C-S-H/C-A-S-H) of alkali-activated slag cements have been found to create instability in their stacks and thus have facilitated the collapsing of these gels, leading to additional autogenous shrinkage in drying conditions [28]. Jeon et al [29] reported that the formation of ettringite in GGBFS-based geopolymer binders counteracts shrinkage in GGBFS-based geopolymer binders effectively [29]. Research on low-calcium FA and bottom ash-based geopolymer concrete, a part of the mixing water, was found to remain associated with the binding gels (N-A-S-H/N-C-A-S-H) [30].…”
mentioning
confidence: 99%
“…The alkali cations present in the binding gels (C-S-H/C-A-S-H) of alkali-activated slag cements have been found to create instability in their stacks and thus have facilitated the collapsing of these gels, leading to additional autogenous shrinkage in drying conditions [28]. Jeon et al [29] reported that the formation of ettringite in GGBFS-based geopolymer binders counteracts shrinkage in GGBFS-based geopolymer binders effectively [29]. Research on low-calcium FA and bottom ash-based geopolymer concrete, a part of the mixing water, was found to remain associated with the binding gels (N-A-S-H/N-C-A-S-H) [30].…”
mentioning
confidence: 99%
“…The isothermal calorimetry method is used to investigate the effects of temperature on the reaction kinetics of cementitious materials [ 40 ]. Figure 7 shows the calorimetric curves of heat release from the UWC specimens with (a) NS and (b) MgO.…”
Section: Resultsmentioning
confidence: 99%
“…The viscosity values of the UWC mixes with NS and MgO were assessed with a rheometer (Rheometer R/S Plus, Brookfield, WI, USA). To observe the setting time of the fresh UWC mixes, paste samples were obtained after mixing the UWC concrete, and the initial and final setting times were investigated using Vicat needles [ 39 , 40 ] according to ASTM C 191 [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Fresh properties i.e., air content and slump of the concrete mixes were examined. Paste specimens were made using a W/B ratio of 0.40 and investigated for heat flow using a semi-adiabatic calorimeter [30,31]. For Fourier transform infrared spectroscopy(FTIR) and XRD analyses, paste specimens were made using a W/B ratio of 0.4 and cured for 3, 7, and 28 days.…”
Section: Proportions and Methodologymentioning
confidence: 99%